Examining pre-service science teachers’ number and space relation skills - Yenikalaycı, Nisa; Akarca, Türkan Aybike (Journal of Turkish Science Education, 2020)
One of the basic science process skills, number and space relation, is used to transform a two dimensional object into a three-dimensional shape or express symmetry axis of the objects. The aim of this research was to determine the number and space relation skills of pre-service science teachers in order to train more qualified science teachers equipped with 21st century skills. The participants were 60 pre-service science teachers, first year students studying in a science education program in a state university located in the Black Sea region of Turkey. The study was conducted in the 2017 fall semester. Integrative Perception Test (IPT) was prepared by researchers to collect data. Within the scope of the IPT, textbooks specific to the field of science were scanned. Then, textbooks’ visuals without symmetrical structure in physics, chemistry, and biology subfields were identified and listed. During the application, participants were asked to complete the missing half of the visual images by using their imagination and three-dimensional perceptions from their visual memories. The data obtained from the test with 30 images (i.e., 10 physics images, 10 chemistry images, and 10 biology images) were descriptively analyzed. Participants received two points for completed images, one point for images with missing parts, and zero points for incorrect/empty images. Results showed that the chemistry test average of the participants was the highest. Furthermore, it was observed that pre-service science teachers were especially successful on the topics of diffraction of waves and formation of shadow in physics, states of matter and acid-base indicators in chemistry, and the structure of DNA in biology, but it was also evaluated that their general number and space relation skills were in an average level. Results suggest that new studies with different age groups or using symmetrical images in teaching new concepts can be useful.